PENGELOLAAN PAKET WISATA DESA BOKOR KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Dealika Putri Amdita; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Bokor Tourism Village is a village located in West Rangsang District, Kepulauan Meranti Regency, Riau Province which is quite well-known and has the potential to become a tourist destination as well as a venue for holding various international scale events. Through this potential, the Bokor Tourism Village management forms a travel composition that is packaged in a tour package to provide convenience for tourists. This study aims to see how the form of stakeholder contributions and the management of Bokor Village tour packages. This study uses descriptive qualitative method. The concept of this study uses management theory. In collecting data, researchers used interviews, observation, literature and documentation using key informants and supporters as sources of data information. The results showed that the Management of Bokor Village Tourism Packages, Kepulauan Meranti Regency, Riau Province was still not optimal, this was evidenced by the implementation that was not running as it should and the lack of oversight from stakeholders. Then another concern is the lack of tourist objects that can be visited in tour packages and road access to Bokor Village. This is due to the absence of assistance from academics, travel agents and other relevant stakeholders. This makes the Bokor Village Tourism Package Management less successful. Keywords: Management, Tour Package, Bokor Village